Penatalaksanaan Fisioterapi Pada Kasus Post Stroke Hemiparese Sinistra Dengan Modalitas Stimulasi Taktil Dan Pelvic Tilting Untuk Meningkatkan Keseimbangan - Ilvia Rema Viani; Wanti Hasmar; Indah Permata Sari (Politeknik Unggulan Kalimantan, 2021)
Background: Stroke is a functional disorder of the brain that is nerve paralysis due to disorders of blood flow such as bleeding (ischemic) and rupture of blood vessels (hemorrhagic) in one part of the brain that makes the blood supply to the brain decreases causing further brain cell death leading to brain function and disability and even death. Patients post stroke hemiparese sinistra experience balance disorders so patients should be given the right treatment, one of which uses tactile stimulation and pelvic tilting. This study aims to find out the management of tactile stimulation and pelvic tilting in improving balance in cases of post stroke hemiparese sinistra. The method used is a case study method with 1 respondent using the sensory test to evaluate stimulus and the Berg Balance Scale (BBS) to measure balance. The results of the study conducted in Rantau Rasau Subdistrict, Jambi City is tactile stimulation and pelvic tilting for 12 times therapy in 5 weeks can improve the balance of post stroke hemiparese sinistra patients. The conclusion of this study is that tactile stimulation and pelvic tilting can improve balance because this exercise can increase sensory implus, Muscle strength and muscle stabilization in the core muscle (core muscle), when the stimulus (stimulation) in the sensory is given then the receptor will send to the central nerve system and release motor (output) adjusted to the environment, stimulation and movements that are constantly repeated will provide information to the supraspinal mechanisme so that there is an integrated pattern of motion and into functional pattern movements and activate stabilization in the core muscles for strengthening of the abdominal muscles aimed at strengthening the flexor muscles and stalling the muscles of the lower back extensor will improve not only the function of the torso but also balance and mobility, to a greater extent, sensory enhancement, muscle strength and stabilization in post-stroke hemiparese sinistra thus improving balance and functional activity